The performance of Bulgarian food markets during reform - Larson, Donald F. (World Bank, 2009)
"Food policy often depends on markets and markets depend on institutions. But how good do institutions have to be before reforms can be launched? Relying on well timed surveys of agricultural prices and a joint study by the Government of Bulgaria and the World Bank on agricultural market institutions, this paper presents evidence that performance in food markets improved following significant policy reforms in Bulgaria, although public institutions remained weak. This suggests that even though strong institutions are preferred to weak ones, it can be costly and impractical to delay policy reforms until work on strengthening institutions is finished. Still, measured performance varied by place and by commodity, suggesting that markets developed at different tempos and that the distribution of benefits from improved markets was uneven. This points to the need to address the costs of adjustment as policies change. The paper introduces a new approach to measure market performance based on composite-error techniques. "--World Bank web site
Includes bibliographical references. - Title from PDF file as viewed on 5/7/2009
Keywords: Food supply -- Bulgaria